Penerapan Metode Fuzzy Multi Criteria Decision Making Pada Sistem Pendukung Keputusan Pemilihan Smartphone - Kahar, Novhirtamely (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2017)
Smartphone can be interpreted as a small computer that has the ability of a phone. The number of users of Smartphone from year to year increase, seen crowded visitors at the Maju Jaya Cell. During this time the average customer who will buy the Smartphone is always confused to choose the Smartphone that suits your needs and capabilities. With this problem, the researcher builds a Decision Support System (DSS) application to choose Smartphone which should be recommended to be purchased by customer by applying Fuzzy Multi Criteria Decision Making (FMCDM) method. This SPK application is expected to be an assistant for employees to assist customers in choosing Smartphones to be purchased. Smartphone selection based on criteria: price, screen size, battery capacity, operating system, RAM, camera, and brand. Desktop-based desktop software application with delphi 7.0 programming. The results of the study indicate that the recommended Smartphone to be selected by the subscribers is the Smartphone which has the highest integral total value using the optimum degree = 0.5. At the end of the implementation will be displayed output in the form of report the results of the calculation and conclusion, which is the best Smartphone recommendations should be purchased by customers.